Single‐Atom Materials: Small Structures Determine Macroproperties. Issue 2 (19th October 2020) - Yang, Jiarui; Li, Wenhao; Wang, Dingsheng; Li, Yadong
Abstract : Single‐atom materials (SAMs) have been widely investigated during the past years, providing many high‐performance materials applied in catalyst, battery, solar cell, and so on. The high performance that SAM exhibit is largely attributed to the microstructure inside the SAM. It is thus essential to realize the goal of regulating the structures, as the chemists wish and deeply comprehend the relationship between the macroproperties and the small structures. However, the concerns above are far from realization and more efforts are necessary to be put into this field. Herein, the regulation on microstructures, the characterization on the microstructures and the relationship between the macroproperties and the small structures are comprehensively summarized and discussed, which are mainly based on the application of SAM in catalyst. Based on the basic information earlier, the challenge and future development of SAM are also proposed, aiming to emerge an overall view and guideline to the research on the next step. Abstract : The single‐atom materials (SAMs) have been explored intensely, but there are still many barriers needed to overcome, which hold back the practical use of SAM. Herein, the main barriers and opportunities are discussed, aiming to provide a guideline for the research on the next step.